Antioxidant and Anti-Inflammatory Activities of Ethanol Extract from Daucus crinitus Desf. - Fellahi Manel; Dib Mohammed El Amine; Bensaid Okkacha (Chemistry Proceedings)
Oxidative stress, a key factor in triggering inflammation, plays a central role in the development of various aging-related diseases, including cancer, Parkinson’s, and Alzheimer’s. In this context, plant phenolics represent a major group of bioactive compounds that act as primary antioxidants, effectively scavenging free radicals and mitigating oxidative damage, thereby helping to counteract these pathological processes. The objective of this work was to examine the phytochemicals present in the ethanol extract of the aerial parts of Daucus crinitus Desf. and to evaluate their anti-inflammatory and antioxidant activities. Phytochemical screening of the ethanol extract revealed the presence of various chemical groups, including tannins, flavonoids, phenolic acids, and coumarins. The biological activity assessment demonstrated that the ethanol extract exhibited promising antioxidant and anti-inflammatory properties. Daucus crinitus may be a valuable source of bioactive molecules with potential antioxidant and anti-inflammatory benefits.